Listening in on Museum Conversations - Leinhardt, Gaea; Knutson, Karen (Rowman & Littlefield Publishers, 2004)
We all know that learning takes place in museums but what does that really mean? Who learns what and how do they learn it? Gaea Leinhardt and Karen Knutson set out to investigate these questions through the conversations of museum visitors. The model they developed from their research owes much to sociocultural theory, and they challenge others to think about certain specific features of the museum experience in order to understand and define learning. They advocate an expanded concept of learning for museums, and for more formal schooling environments. Leinhardt and Knutson add their voices to what they call the extended conversation that is ongoing among thoughtful practitioners with an interest in formal and informal learning in museums.